2011 IEEE International Symposium on Multimedia 2011
DOI: 10.1109/ism.2011.67
|View full text |Cite
|
Sign up to set email alerts
|

Utterance Rate Feedback for Enhancing Mealtime Communication

Abstract: The purpose of this research is to support users' mealtime communication by changing their utterance rate during meals. By logging and analyzing the utterance rate, or the ratio of utterance length to mealtime length, we determined the relationship between the utterance rate and the distribution of the community to which each meal companion belonged. Using this relationship, we developed a real-time feedback system that presented a pre-estimated utterance rate with rate at the present time during a meal. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Ogawa et al attempted to enhance mealtime communication through lifelogging, and they developed a system called "Vocalog" [11]. Lifelogging refers to the logging of human life in the form of images, movies, sounds, location information, and so on.…”
Section: Supporting Mealtime Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ogawa et al attempted to enhance mealtime communication through lifelogging, and they developed a system called "Vocalog" [11]. Lifelogging refers to the logging of human life in the form of images, movies, sounds, location information, and so on.…”
Section: Supporting Mealtime Communicationmentioning
confidence: 99%
“…Though non-verbal communication is also important, non-verbal communication alone is insufficient and inconvenient for building relationships between people. However, Ogawa et al found that many people who do not talk with others during mealtimes [11]. To solve this problem, they attempted to enhance the amount of individual utterances during mealtimes by displaying a pre-estimated utterance rate along with each individual's actual rate.…”
Section: Introductionmentioning
confidence: 99%